Issues on the residents' perceptions of the impacts of tourism development: the case-study of Guimar\~aes - Paula Remoaldo; Laurentina Vareiro; José Cadima (European Regional Science Association (ERSA), 2011)
In recent years peripheral regions, such as Guimar\~aes, in the Northwest of Portugal, has been experiencing the expansion of its tourism industry. This occurred, may be, as part of the wish felt by a large number of tourists of reaching "unspoilt" landscapes and more "authentical" experiences (Nepal, 2008). After the nomination by U.N.E.S.C.O., in 2001, of its historical centre as world heritage, the city of Guimar\~aes is now in the process of hosting the 2012 European Capital of Culture. These recent facts helped to reinforce its external visibility and cultural significance and put it in the trail to become a more consolidated cultural tourism destination. This paper aims presenting a few results of a survey that envisaged capturing the Guimar\~aes residents' perceptions of tourism effects and attitudes regarding the tourists. The survey was implemented between January and March 2010 to a convenience sample of 540 inhabitants of the municipality of Guimar\~aes. The results show that the Guimar\~aes` residents keep a strong positive perception of the tourism benefits. The more or less favourable perception of tourism impacts the survey respondents kept are strongly correlated with some demographic features, such as age, gender and level of education. As expected, we got a more positive perception among the younger cohorts of age and the ones endowed with a higher level of education.
Keywords: 330